UTILIZATION OF BRAN FLOUR AS AN INGREDIENT IN THE PRODUCTION OF BREAD IN STPBI - Ida Bagus Soma; I Wayan Arcana (Institut Pariwisata dan Bisnis Internasional, 2015)
Indonesia is an agricultural country where the livelihoods of the majority of the population to grow crops. Geographically Indonesia is an archipelago which also has great natural potential not only in the field of marine but also in agricultural processing. One of the results is a leading Indonesian agriculture is rice. It is not apart from the fact that rice as a staple food of Indonesia. In this study, researchers will describe the manufacturing process and the final result in the making of bread made from bran flour. Where researchers will create four kinds of bread, which is bread without flour bran as quality control (P0), white bread with a mixture of 10% flour bran (P1), white bread with a mixture of 20% flour bran (P2), and bread with 30% bran flour mixture (P3). Objects were observed in this study was to determine the final result of the manufacture of bread to test the texture, color, flavor, and aroma with a mixture of flour bran, the method of making the same, cooking equipment are the same, long fermentation time the same, the temperature of the oven the same and roasting the same time.